1991
DOI: 10.1007/bf01300087
|View full text |Cite
|
Sign up to set email alerts
|

Visceral perception in health and functional dyspepsia

Abstract: The symptoms of functional dyspepsia are still unexplained. To evaluate the possible role of abnormal visceral perception, we studied the symptomatic responses and the pressure variations during progressive gastric distension in 10 female healthy control subjects (mean age 33.6 years) and in 10 female patients with functional dyspepsia (mean age 35.2 years). A rubber balloon was positioned 4 cm below the lower esophageal sphincter (LES) and inflated with progressively larger volumes of air by steps of 50 ml; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…As in many previous studies of the sensory function in patients with FD [3, 4, 5], we observed visceral hypersensitivity in the fasting state in these patients. Gastric hypersensitivity to mechanical balloon distention has been a common finding in most studies on FD comparing sensory thresholds between patients and controls, although this has been shown to be an inconsistent finding [29].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As in many previous studies of the sensory function in patients with FD [3, 4, 5], we observed visceral hypersensitivity in the fasting state in these patients. Gastric hypersensitivity to mechanical balloon distention has been a common finding in most studies on FD comparing sensory thresholds between patients and controls, although this has been shown to be an inconsistent finding [29].…”
Section: Discussionsupporting
confidence: 87%
“…Functional dyspepsia (FD) is a heterogeneous disorder associated with delayed gastric emptying [1, 2], as well as gastric hypersensitivity to mechanical stimulation [3, 4, 5]and impaired accommodation of the proximal stomach [6, 7]. According to the Rome II criteria [8], patients with FD can be subdivided into ulcer-like dyspepsia (ULD) and dysmotility-like dyspepsia (DLD) based on the most bothersome symptom, which is pain in ULD and discomfort in DLD.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms in non‐ulcer dyspepsia patients may be influenced by various factors including acid secretion, gastric perception, food, psychological factors, biliary tract function, enterogastric bile and other unknown factors 35 –40 . Our data suggest that disturbed gastric emptying caused by H. pylori is one of the factors causing the symptoms in non‐ulcer dyspepsia patients because gastric emptying and symptom score improved significantly, paralleling the eradication therapy in the delayed and rapid gastric emptying groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kingham and Dawson [57] describe a study in which a latex balloon was swallowed and inflated, producing a pain sensation similar to that reported in naturally occurring GI pain. Bradette et al [9] also examined upper GI stimulation by inserting a balloon at the gastric side of the lower oesophageal sphincter, which was found to successfully induce pain in both patients and healthy participants. These techniques seem to be particularly useful for those interested in studying sensations of fullness, pressure, and general pain.…”
Section: Analogue Versions Of Visceral Painmentioning
confidence: 99%